(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
This work focuses on studying the effect of adding nanoparticles on the mechanical properties of the alloy (Al-4%Si) reinforced with carbon nanotube at a different weight percentage (0.25,0.5 and 1%wt). prepared the base alloy and the reinforced materials in a casting followed by solution heat treatment in the furnace at temperature 520ºC for 2 hr. , then artificially aged immediately at the temperature of 185 Co for (2-8 hr.). A detailed characterization of the composite metal matrix structure has performed using XRD, microhardness and wear rate measurements. The results demonstrated that the values of the hardness test increase with an increasing weight percentage of CNTs, this enhancement wear properties of the base alloy reinforced for all percentage of carbon nanotubes additive especially at the weight percentage of 0.5%.